DAMPAK COVID-19 TERHADAP SOSIAL EKONOMI PENENUN ULOS DI DESA SITOLUHUTA KABUPATEN SAMOSIR - Pasaribu, Riris Nauli; Atika, Tuti (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2022)
The existence of the Corona virus Disease 2019 (COVID-19) pandemic has had a major impact on various sectors. The government's policy to implement Large-Scale Social Restrictions (PSBB) related to the COVID-19 pandemic has had an impact on the sustainability of Micro, Small and Medium Enterprises (MSMEs). The COVID-19 pandemic has an impact on the Ulos Weavers in Sitoluhuta Village because various activities Cultural have been temporarily postponed and abolished in the implementation of government policies during the pandemic. This study aims to determine how the impact of the COVID-19 pandemic on the socio-economic conditions of ulos weavers in Sitoluhuta Village. The type of research used is descriptive research with a qualitative approach. Data collection techniques were carried out by collecting primary data (interviews, observations) and secondary data (library research, documentary studies). The main informants in this study consisted of 5 people who worked as ulos weavers. The results showed that the COVID-19 pandemic had a major impact on ulos weavers in Sitoluhuta Village. Where is the impact experienced by ulos weavers during the covid-19 pandemic, declining prices and marketing of ulos, resulting in a decrease in weavers' income. Another impact felt by ulos weavers during the pandemic is the increasing expenditure in meeting children's educational needs and the need for clothing and food as well as the emergence of the weaver's fear of interacting with the surrounding environment.